Lokalklima und Vegetation im Kirishima-Gebirge im südlichen Kyûshû, Japan - Yoshino, Masatoshi M.; Yoshino, Midori T. (ERDKUNDE, 1963)
Local differences of air temperature, precipitation and wind conditions in the Mt. Kirishima region were firstly described. The summit areas above 1400 m in this region have Koppen's D-climate. The distribution patterns of precipitation do not coincide with those of 500 and 1000 m contour lines, but differ according to synoptic situations, such as extra-tropical cyclones, typhoons, or orographic rains. The lapse rate of maximum temperature is greater than that of minimum temperature. The greater cloudiness, the greater lapse rate. The lapse rate in summer is smaller than that in winter. According to the results of the observation from the microclimatological viewpoint, the wind velocity at the windward top of the outside of the crater is two-thirds to three-fifths of the free air wind velocity observed by radio-sonde at Kagoshima. On the contrary, that at the lee side is one-fourth to one-fifth. Distribution of vegetation in this region is then studied in detail. To compile a vegetation map, an attempt was made from aerial photographic interpretation, referring the data accumulated at the forestry stations and obtained by field survey. In this region, vegetation is classified into twelve types as follows : 1. Laurel forest. 2. Natural coniferous forest. 3. Deciduous scrub forest. 4. Grassland. 5. Bare land. 6. Forest mixed with big deciduous trees. 7. Afforested area of mixed conifers. 8. Afforested area of japanese ceder forest. 9. Afforested area of japanese cypress forest. 10. Afforested area of japanese red pine forest. 11. Young forest (species are not distinguished on aerial photographs). 12. Cultivated field. In general the following vertical zonation of vegetation can be distinguished: 1. Laurel forests up to the height of 800 m. 2. Natural coniferous forests from 800 m to 1400 m. Among them, the forests, which consist of the coniferous trees in upper layer with evergreen broad leaved trees in middle and lower layers, appear from 800 m to 1000 m. Then the forests, which consist of the coniferous trees in upper layer with deciduous broad leaved trees in middle and lower layers, appear from 1000 m to 1400 m. 3. Deciduous scrub forests near the steep mountain tops and ridges or surrounding the active cones. 4. Grassland including the bambusaceae and other bush area on the windy summits. Natural coniferous forests mainly occupy the northern part of the region, where annual precipitation exceeds 4000 mm and soils show a good development. Deciduous forests cover the southern part of this region, where two volcanic cones have often caused forest fires by their ejecta. Therefore, it can be said that the secondary vegetation of deciduous scrub, as a result of forest fires, appears on the leeside of the active cones under the influence of the prevailing upper westerly winds.